Doctor's Liability to Patient Due to Default in Therapeutic Agreement (Case Study of Ma RI Decision Number 2811 K/Pdt/2012) - Fatoni, Galih; Nurhayati, B. Resti; Nugroho, Hari Puja (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The legal relationship that occurs between a doctor and a patient is called a Therapeutic Agreement/Transaction. Risks that can cause harm to patients can occur in even the smallest medical procedures. A doctor can be held liable if he has made a mistake or negligence and caused harm, although basically no doctor intentionally makes a mistake as happened in the Indonesian Supreme Court Decision Number 2811K/Pdt/2012. The type of research used by the author is normative juridical, namely legal research carried out by examining library materials or often also referred to as library legal research. The results of the research carried out were obtained by the judge's consideration in the Indonesian Supreme Court Decision Number 2811K/Pdt/2012 which was inaccurate, because according to the Supreme Court judge, the cassation respondent's actions were correct and did not violate any legal provisions. In fact, after a description of the facts in the series of events in this case, it was clearly found that the doctor and hospital had done things that violated the provisions of the Health Law, including violating the Medical Code of Ethics. The actions of the cassation respondent, especially doctor E and including doctor J as the recipient of the delegation, have been proven to be in breach of contract. This is because the actions of the two doctors violated the provisions of the Medical Practice Law, namely that the actions they took were not in accordance with standard procedures and violated the provisions of the law.